Effects of Synthetic Procedures and Postsynthesis Incubation pH on Size, Shape, and Antibacterial Activity of Copper (I) Oxide Nanoparticles - Vinh Tien Nguyen; Khanh Son Trinh (Journal of Chemistry)
Copper (I) oxide nanoparticles (Cu2O NP) were synthesized by reducing CuSO4 with glucose in the presence of polyvinyl alcohol as a capping agent. We used three different synthetic procedures with a fast reaction (procedure 1p), a fast-then-slow reaction (procedure 2p), and a slow-then-fast reaction (procedure 3p). The reaction rates were controlled by changing the temperature and the speed of adding reagents. The synthesized Cu2O NP were subsequently incubated for 24 h in a pH 6 solution (Cu2O NP6) or a pH 8 solution (Cu2O NP8) at 5°C. XRD and SEM images analysis revealed that the 1p procedure produced smaller NP, while the 2p procedure produced larger but more uniform NP. The 3p procedure produced the largest NP with a higher size variation. The 24-hour acidic postsynthesis incubation resulted in an etching effect, which reduced the size and size variation of Cu2O NP6. To evaluate the antibacterial activity, E. coli suspensions were mixed with the obtained Cu2O NP (32, 96, or 160 ppm) for different time intervals (1 or 24 h) and then grown on Petri dishes at 37°C for 24 h. Higher doses, smaller sizes of Cu2O NP, and longer contact times with the bacterial suspension resulted in higher inactivation efficiencies. Cu2O NP6 showed higher antibacterial effects at low doses, possibly due to the etching effect and the positive surface charge. Increasing the Cu2O doses from 32 to 96 and 160 ppm noticeably increased the antibacterial effect of the Cu2O NP8, but not significantly for Cu2O NP6. We suggested that the Cu2O NP6 suffered from agglomeration at high doses due to their high surface activity and low surface charges.